International Experience Of Forming Research Skills In Students - Asadova, Sitora Sadullayevna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This thesis provides an in-depth analysis of developing instructional design competencies among prospective teachers as a contemporary pedagogical challenge. The pressing aspects of the issue are revealed through a comparative study of international (USA, Finland, Singapore, Australia) and local practices. The research encompasses the structural components of instructional design skills, including analytical, prognostic, constructive, creative, and technological competencies. The article presents modern strategies for preparing prospective teachers based on the TPACK (Technological Pedagogical Content Knowledge) model, Design Thinking approach, and reflective practice. Analysis of recent international research from 2023-2024 (Scopus, Web of Science) demonstrates that instructional design competencies play a crucial role in developing critical thinking, creative problem-solving, and collaborative skills. The author proposes a systematic approach to addressing this issue in teacher education institutions.